2004
DOI: 10.1002/gcc.20093
|View full text |Cite
|
Sign up to set email alerts
|

Benzo[a]pyrene diol epoxide‐induced 9p21 aberrations associated with genetic predisposition to bladder cancer

Abstract: CDKN2A, 9p21, encodes two alternatively spiked, functionally distinct, tumor-suppressor proteins, P16INK4A and P14ARF, which play active roles in the RB1 and TP53 pathways, respectively. Deletion of 9p is one of the most frequent genomic alterations in bladder cancer. In addition, alterations of 9p21 and P16 are frequently seen in the epithelial cells of chronic smokers. This pilot study evaluated whether 9p21 aberrations induced by exposure in vitro to benzo[a]pyrene diol epoxide (BPDE), the metabolic product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Chromosome 9p21 has been found to be a molecular target for damages induced by benzopyrene diolepoxide (BPDE), the metabolic product of benzopyrene, a constituent of tobacco smoke. 26 Smoking seems to affect the pattern of TP53 mutations, but have no effect on the incidence and pattern of FGFR3 mutation. 27 Consistently, occupational exposure to polycyclic aromatic hydrocarbons, which are also commonly found in cigarette smoke, did not influence the frequency or spectrum of FGFR3 mutations.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Chromosome 9p21 has been found to be a molecular target for damages induced by benzopyrene diolepoxide (BPDE), the metabolic product of benzopyrene, a constituent of tobacco smoke. 26 Smoking seems to affect the pattern of TP53 mutations, but have no effect on the incidence and pattern of FGFR3 mutation. 27 Consistently, occupational exposure to polycyclic aromatic hydrocarbons, which are also commonly found in cigarette smoke, did not influence the frequency or spectrum of FGFR3 mutations.…”
Section: Discussionmentioning
confidence: 97%
“…Zhang et al 25 found that chromosome 9 alterations were more common in smokers compared to those in nonsmokers. Chromosome 9p21 has been found to be a molecular target for damages induced by benzopyrene diolepoxide (BPDE), the metabolic product of benzopyrene, a constituent of tobacco smoke 26 . Smoking seems to affect the pattern of Tp53 mutations, but have no effect on the incidence and pattern of FGFR3 mutation 27 .…”
Section: Discussionmentioning
confidence: 99%
“…In DR4 exon 4, a C-G polymorphism at amino acid 626 is located immediately 3 0 to one of the main receptor ligand interface regions, which results in a threonine-arginine change (Fisher et al, 2001). Hazra et al (2003) found that the DR4 exon 4 G/G genotype was associated with an overall 42% decreased risk of bladder cancer in Caucasians. This protective effect was more apparent in younger individuals, women and light smokers.…”
Section: Apoptosismentioning
confidence: 95%
“…BPDE Sensitivity Assay. FISH was used to measure BPDE-induced 9p21 aberration as previously described (14). Briefly, whole blood (1 mL) was cultured in 9 mL of RPMI 1640 (JRM Biosciences) with 20% FCS and 1.25% phytohemagglutinin (Wellcome Research Laboratories) at 37jC for 72 h. BPDE was added at the final concentration of 2 Amol/L for 24 h. After routine blocking with colcemid, hypotonic treatment, and fixation, cell suspensions were stored at À20jC until processing for FISH experiments.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, measuring these specific chromosome aberrations may have the potential to predict an individual's genetic susceptibility to tobacco-related cancer. In an earlier pilot case control study of bladder cancer, we tested 9p21 sensitivity to BPDE using locus specific fluorescence in situ hybridization (FISH) technique and revealed that 9p21 may be a hotspot for BPDE and 9p21 sensitivity to BPDE may be associated with an increased risk of bladder cancer (14). In this current report, we tripled the sample size and validated previous findings from the pilot study (14) that BPDE-induced 9p21 aberration is associated with an increased risk of bladder cancer.…”
Section: Introductionmentioning
confidence: 99%